Management of Acidic Mine Waste Water by Constructed Wetland Treatment Systems: A Bench Scale Study - Sheoran, A.S. (European Journal of Sustainable Development, 2017)
Constructed wetlands have emerged as a viable option for treatment of acidic mine wastewater. Bench scale experiments were conducted, to evaluate the performance of wetland treatment system, with emergent macrophyte Desmostachya bipinnata and substrate (containing powdered goat manure, wood shavings and soil) for 24, 48, 72, 96 and 168 hours of retention period for different water column heights (100mm, 150mm and 200mm). Within 24 hours of retention period the pH increased from 2.93 to 7.22, alkalinity increased from zero mg/L to 204.30 mg/L as CaCO3, electric conductivity decreased by 27.94 to 35.93 percent, turbidity decreased by 30.14 to 66.65 percent, sulphate reduced by 21.52 to 28.09 percent, acidity reduced by 88.89 to 100 percent, hardness reduction was 18.18 to 26.07 percent. Potential metal removal rates was 95.20 to 95.51 percent for Fe, 88.77 to 91.72 percent for Cu, 76.75 to 78.21 percent Zn, 88.80 to 90.12 Pb, 67.65 to72.33 percent Co, 29.60 to 63.76 percent Ni and 35.90 to 76.44 percent Mn respectively. Keywords: Acidic Mine Water,Treatment, Constructed Wetland, D. bipinnata